Kidney Transplantation : Strategies for Expanding Donor Pool (Bangladesh Journal of Urology, 2020)
Objective: To find out the appropriate strategies to increase the donor pool for kidney transplantation.Methodology: The PubMed literature database was searched from 2015 to 20 years backward. Strategies to increase and improve live donor KT were suggested. In order to formulate some suggestions to reach that target, related experience and strategies published in journals of last 20 years both from developed and developing countries, were reviewed.Results: Strategies to increase and improve live donor KT were suggested .Only Live donor KT can never fulfil the demand of KT. The most important step to boost up KT program is to start deceased Donor Organ Transplantation and by formulating a law and establishing infrastructure. Development of National Kidney Transplant Registry and coordination of KT at National level is also very important. Those patients who cannot afford expenditure for KT and post-transplant care, can be supported by raising fund at national and international level.Conclusion: To increase living donor KT, techniques of increased graft survival, donor and recipient comfort, confidence and safety should be established . Inclusion of both brain death (BD) and Deceased Circulatory Death (DCD) in Deceased Donor pool will be good option for increasing donor pool.Bangladesh Journal of Urology, Vol. 18, No. 2, July 2015 p.88-93